From gut dysbiosis to decidual hostility: the immuno-metabolic crosstalk driving recurrent pregnancy loss - Shi, Yimin; Tang, Xiufeng (Frontiers in Immunology, 2026)
Recurrent pregnancy loss (RPL), particularly its unexplained form (URPL), represents a formidable challenge in reproductive medicine. Although traditionally attributed to local immune imbalances at the maternal-fetal interface, this perspective may not fully account for the condition’s upstream etiological drivers and recurrent nature. This review transcends this limitation by proposing and systematically substantiating an integrative ‘gut-systemic-decidual’ model of immunometabolic dysregulation. We posit that a key pathological cascade in many URPL cases may originate with distal gut dysbiosis, which, through imbalanced metabolite profiles and the leakage of inflammatory molecules such as lipopolysaccharide (LPS), triggers systemic ‘metabolic endotoxemia’ and fundamentally reprograms the metabolic state of circulating immune cells. This systemic ‘first hit’ is compounded when these ‘pre-sensitized’ cells migrate to an equally metabolically stressed and ‘hostile’ decidual microenvironment—a ‘second hit’ characterized by hypoxia and high lactate. This culminates in the functional collapse of the core sentinels of maternal-fetal tolerance, namely regulatory T (Treg) and decidual natural killer (dNK) cells, due to profound metabolic misprogramming. Ultimately, this integrated model elevates the etiological understanding of URPL from a ‘local conflict’ to that of a ‘systemic disease,’ paving the way for the development of dynamic warning systems that integrate multi-omics data and for the design of multi-level precision intervention strategies targeting patient stratification and preventive approaches for the gut, systemic metabolism, and the local microenvironment.